International cooperation on financial market regulation - Michael Abendschein; Harry Gölz (International Economics and Economic Policy, 2021)
At the latest the global financial crisis has raised the awareness of the need for a globally coordinated financial market regulation. Even though the necessity to cooperate is widely acknowledged, cooperation is often limited in practice. This article characterizes the formation of self-enforcing international financial regulation agreements. Our analysis allows to evaluate the desirability and feasibility of cooperative solutions and explains the challenges associated with the process of cooperation. We model the cooperation of national financial regulators in a game-theoretical framework that considers financial stability to be an impure public good. Joint national supervisory effort is supposed to increase aggregate welfare in terms of a more stable financial system both on a global and on a local level by simultaneously generating incentives to free-ride. Our analysis in general indicates the difficulty of reaching a fully cooperative solution. In our basic version of the model we show that partial cooperation of two or three countries is stable and improves the welfare of all countries relative to the non-cooperative Nash equilibrium. Further analyses highlight the role of additional club benefits. When signatory countries of a coalition gain benefits over and above the joint welfare maximization, stable coalitions of any size become feasible.
Keywords: C72; F53; G18; H87; 330; Financial Stability; International Policy Cooperation; Bank Regulation; Non-Cooperative Game; Impure Public Good